The effects of gamified flipped instruction on learner performance and need satisfaction: A study in a low-tech setting. Issue 11 (11th November 2019) - Zainuddin, Zamzami; Shujahat, Muhammad; Chu, Samuel K.W.; Haruna, Hussein; Farida, Ratna
Abstract : Purpose: This study aims to assess students' learning performance and perceived need satisfaction between a gamified flipped classroom (GFC) and flipped classroom (FC) instruction in a low-tech setting. The iSpring Learn learning management system was used as a low-tech gamification application in gamifying the flipped learning class. Design/methodology/approach: A quantitative research approach was used for collecting the data. Three formative assessments were used to examine students' learning performance during the intervention period, and a post-questionnaire survey was used to support the data collection process with regard to students' perceived needs satisfaction. In total, 56 students were involved in a non-randomised experiment with a control group design. Findings: The results reveal that Assessment 1 showed no significant difference between the two intervention groups ( p > 0.05), while Assessments 2 and 3 were significantly different ( p < 0.05). The survey results confirm that participants in the GFC have achieved a great level of motivation because their innate psychological needs for competence, autonomy and relatedness are satisfied. Practical implications: The use of game-like features can be a powerful means to produce more engaging and fun activities in the FC context. The study has confirmed that integrating the gamification concept into FC instruction by adding challenges, incentives, points and rewards to quiz questions promoted a more engaging and enjoyable experience for learners. Originality/value: Gamification as a current concept of a twenty-first-century instructional skill has proven to be remarkably influential. This study suggests that the FC and gamification concept might be possibly implemented in a low-tech information environment – without the required advanced technology platform.